(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Since its initial identification with primary effusion lymphoma (PEL), the range of lymphoproliferative illnesses associated with human herpesvirus 8 (HHV-8) infection has steadily expanded. Systemic B cell lymphoma often has p16(INK4a) and p15(INK4b) inactivation, which may indicate a poor prognosis. 200 specimens are studied cross-case-control. Lymphoma (LY) patients and normal people (control group) are sampled. Iraq’s Middle Euphrates region’s general hospitals and private clinics provided the samples. The study included 17-75-year-olds. Samples were collected between October 2022 and February 2023. PCR-based sequencing detected HHV-8 and p15 gene polymorphisms. Materials and Methods: PCR was used to detect HHV-8 and P15 gene polymorphism in 100 patients and 100 healthy individuals. Conventional PCR sequenced HHV-8 and p15 gene polymorphisms Results: 31 out of 64 (48.4%) specimens tested positive for HHV-8, while 33 out of 64 (51.6%) tested negative. The age group (56-75 years) has 48% of HHV8-infected lymphomas, while the age groups (15-35 years) and (36-55 years) had 23% and 29%, respectively. The P15 polymorphism shows that the AA genotype increased lymphoma, while the TT genotype decreased it (p<0.05). Conclusion: Despite the small sample size, our findings suggest that HHV-8 and p15 gene polymorphism may affect lymphocyte tumor biology and development.